The Urgency of Regulating Trading in Influence: An Analysis of the Doctrine of Participation in Indonesian Criminal Law - Sitorus, Talenta; Rusmiati, Elis; Sulistyani, Wanodyo (Corruptio, 2024)
Trading in influence is a non-mandatory offense regulated under the United Nations Convention Against Corruption (UNCAC). Indonesia ratified the UNCAC through Law Number 7 of 2006. In practice, trading in influence has been prevalent in Indonesia; however, it is often prosecuted as bribery. Perpetrators are typically charged under Article 55 of the Criminal Code (concerning participation) in conjunction with bribery or gratuity provisions under the Corruption Eradication Act. This research employs a normative legal research method, analyzing laws, legal literature, and doctrines related to the concept of influence trading. The findings indicate an urgent need for explicit regulation of trading in influence within Indonesia’s legal framework. The current anti-corruption laws, particularly when applied alongside Article 55, do not comprehensively address cases where influence trading occurs without direct bribery but still results in financial losses to the state. Establishing clear legal provisions on trading in influence is essential to prevent legal uncertainty and close existing regulatory gaps.